2021
DOI: 10.3389/fmed.2021.763773
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow-Resident Vδ1 T Cells Co-express TIGIT With PD-1, TIM-3 or CD39 in AML and Myeloma

Abstract: Background: γδ T cells represent a unique T cell subpopulation due to their ability to recognize cancer cells in a T cell receptor- (TCR) dependent manner, but also in a non-major histocompatibility complex- (MHC) restricted way via natural killer receptors (NKRs). Endowed with these features, they represent attractive effectors for immuno-therapeutic strategies with a better safety profile and a more favorable anti-tumor efficacy in comparison to conventional αβ T cells. Also, remarkable progress has been ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 69 publications
(109 reference statements)
1
21
0
Order By: Relevance
“…In both myeloid leukemia and multiple myeloma, using flow cytometry, the bone marrow resident γδ T cells, a T cell subpopulation of non-MHC-restricted, have shown TIGIT, PD-1, TIM3, and the ectonucleoside triphosphate diphosphohydrolase-1 (CD39) co-expression at a high level compared to αβ T cell but similar to that expressed on CD8 + effector T cells ( 139 ). These markers were linked to signs of exhaustion, such as transcriptional reprogramming, decreased release of proinflammatory cytokines, decreased T cell proliferation, and lesser tumoricidal activity, and were associated with a lower OS for myeloid leukemia ( 139 , 140 ).…”
Section: Tigit In Cancer Progressionmentioning
confidence: 99%
“…In both myeloid leukemia and multiple myeloma, using flow cytometry, the bone marrow resident γδ T cells, a T cell subpopulation of non-MHC-restricted, have shown TIGIT, PD-1, TIM3, and the ectonucleoside triphosphate diphosphohydrolase-1 (CD39) co-expression at a high level compared to αβ T cell but similar to that expressed on CD8 + effector T cells ( 139 ). These markers were linked to signs of exhaustion, such as transcriptional reprogramming, decreased release of proinflammatory cytokines, decreased T cell proliferation, and lesser tumoricidal activity, and were associated with a lower OS for myeloid leukemia ( 139 , 140 ).…”
Section: Tigit In Cancer Progressionmentioning
confidence: 99%
“…Although γδ T cells were applied to adoptive cell therapy of ccRCC for decades, studies for the identification of autologous tumor‐reactive γδ T cells have been limited. Previous studies 13,18,19 and our bioinformatic analysis indicated that ccRCC patients with high TIGIT expression showed stronger antitumor response.In the further study, we demonstrated that the TIGIT expression is associated with the activation of γδ T cells triggered by ZOL. More interestingly, TIGIT + γδ T cells exhibited enhanced activation, stronger tumor reactivities and higher cytotoxicity when challenged by tumor cells.…”
Section: Discussionmentioning
confidence: 64%
“…We chose NDMM as a control group to avoid the impact of other drugs given before DARA on the BM microenvironment. Brauneck et al found that CD8 + T-cells from NDMM showed an increased expression of PD-1 and TIGIT compared to healthy controls [ 34 ]. As we did not include a group of healthy controls, we were unable to perform the same comparison; however, we found no correlation between the expression of checkpoint molecules on CD8 + T-cells and response to first line treatment.…”
Section: Discussionmentioning
confidence: 99%